STUNTING PROGRAM STRATEGY EFFECTIVE IN BUALO VILLAGE - Ramin Musa; Imam Mashudi; Fibriyanti Lakoro (Journal of Economic, Business, and Administration (JEBA), 2021)
The purpose of the study was to determine the form of an effective stunting management program strategy in Bualo Village. This research is a type of descriptive research with a qualitative approach. Data collection methods used in this study were observation, in-depth interviews (indept interviews) and documentation. The data analysis technique used in qualitative research is carried out before entering the field, during the field and after completing the field. The results showed that the organizational strategy in stunting handling was considered to be very supportive of stunting handling and was considered to have supported effective stunting management. Program strategies in handling stunting were less capable in handling stunting in reducing stunting rates in Bualo Village. and reducing the stunting rate in Bualo Village. The institutional strategy in handling stunting is maximized because it is still improving the handling of stunting in Bualo Village.